Application of Project-Based Learning Model to Improve Learning Outcomes and Critical Thinking Abilities in Nautical Skills Learning: Penerapan Model Pembelajaran Berbasis Proyek untuk Meningkatkan Hasil Pembelajaran dan Kemampuan Berpikir Kritis pada Pembelajaran Kecakapan Bahari - Kurniadi, Dedy; Baihaqi; Sultan; Nurmala, Eka; Mashuri, Kahar (PT. Alpha Trianguli Australis, 2024)
Some students at shipping education institutions feel that learning nautical skills is one of the courses that is not very popular, it greatly affects the attitude and results of learning nautical skills. This research is important to be carried out to improve the quality of nautical skills learning through project-based learning methods by inviting students to complete projects that must be done which they will also face in the world of work. This research is a classroom action research that uses a qualitative approach with the lesson study method. The results of this research are expected to be useful for educators in educational institutions in the shipping sector in applying a new model to improve learning outcomes and critical thinking skills.